Bioconstruction in Latin America: a redemption from the pandemic crisis (2022)
The covid-19 pandemic has increased the economic, social and environmental crisis that Latin American countries are experiencing. Bioconstruction is proposed as a way to redeem, or rescue the planet from its eminent devastation, through the promotion of low-polluting local natural materials and techniques. In contrast, the conventional construction of reinforced concrete or fired partition, generates 39% of the greenhouse effect, as a result of the transfer of materials, their firing or the use of machinery, so it is important to reduce it. The objective of this work is to analyze bioconstruction as a proposal to promote decent habitats, as well as to reduce the emission of polluting gases in Latin American countries. The methodology is based on the analysis of bioconstruction considering indicators such as: its impact or scope, projection or scalability, innovation and budget supported by empirical experience in cases developed in countries such as Bolivia, Peru and Argentina. The results show advantages in the works carried out based on bioconstruction, highlighting the benefits in terms of duration, efficiency, humidity and temperature. It is concluded that bioconstruction represents an opportunity in Latin American countries to face the crisis that prevailed before the appearance of the pandemic, but that has increased due to the arrival of covid-19